2002
DOI: 10.1152/physiolgenomics.00076.2002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological significance of two common haplotypes of human angiotensinogen using gene targeting in the mouse

Abstract: Angiotensinogen (AGT) was the first gene to be genetically linked to hypertension in humans. Analysis of the gene sequence identified a number of polymorphisms, several of which were reported associated with increased blood pressure (BP) or other cardiovascular diseases. One haplotype of the human AGT (hAGT) gene consisting of an allele at the -6 (A vs. G) position in the promoter and the sequence encoding amino acid 235 (Thr vs. Met) attracted the most attention and has been the subject of numerous associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
(57 reference statements)
2
20
1
Order By: Relevance
“…To determine the contribution of renal AT 1 Rs in the regulation of blood pressure, Crowley et al studied the effect of transplanting kidneys from AT 1A Ϫ/Ϫ mice into bilaterally nephrectomized wild-type nontransgenic mice, and vice versa. 13 These investigators estimated that basal blood pressure control resides in AT 1 Rs inside and outside the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the contribution of renal AT 1 Rs in the regulation of blood pressure, Crowley et al studied the effect of transplanting kidneys from AT 1A Ϫ/Ϫ mice into bilaterally nephrectomized wild-type nontransgenic mice, and vice versa. 13 These investigators estimated that basal blood pressure control resides in AT 1 Rs inside and outside the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…G enetic manipulations that increase the activity of the renin-angiotensin system (RAS) systemically [1][2][3][4][5] or in specific organs (eg, brain and kidney) elevate blood pressure. 6,7 For example, overexpression of angiotensinogen and renin in renal proximal tubules 6 or in neurons and glia cells in brain 7 increased blood pressure without increasing circulating renin levels.…”
mentioning
confidence: 99%
“…However, the transcriptional regulation by -6A nucleoside as compare to -6G is not known. Nevertheless, the transgenic studies demonstrate that this polymorphism neither changes the expression of the AGT nor increases blood pressure [55]. In conclusion, inhibition of the RAS in experimental animals and clinical studies has proven effective in counteracting fibrosis, cirrhosis, and hypertension [6,13,14,16].…”
Section: Pathophysiologymentioning
confidence: 86%
“…Some previous studies revealed that the T174M variant was in tight linkage disequilibrium with other variants such as coding region variants, promoter variants and other yet unknown functional AGT polymorphisms. 5,[42][43][44] Therefore, it is necessary to evaluate the combined effect of T174M with other relevant polymorphisms in the AGT gene or different genes. The results from Yuan et al 13 suggested there was no evidence of association between T174M polymorphism by itself with hypertension in the Hani minority in China.…”
Section: Discussionmentioning
confidence: 99%